Abundant proteins in platelet-rich fibrin and their potential contribution to wound healing: An explorative proteomics study and review of the literature - Emre Yaprak; Murat Kasap; Gurler Akpinar; Eylul Ece Islek; Alper Sinanoglu (Elsevier, 2018)
Background/purpose: It is well-known that diverse types of blood proteins contribute to healing process via different mechanisms. Presence and potential involvements of blood-derived abundant proteins in the platelet-rich fibrin (PRF) to its regenerative capacity have not been sufficiently emphasized in the literature. The aim of this paper was to analyze the abundant proteome content of PRF and summarize previously reported effects of identified proteins on wound healing via a literature review. Materials and methods: The PRF samples obtained from non-smoking, systemically healthy volunteers were subjected to 2D gel electrophoresis after extracting the proteins from fibrin matrices. All matching spots were excised from the gels and identified by MALDI TOF/TOF MS/MS analysis. A literature review was conducted to reveal possible contributions of identified proteins to wound healing. Results: Totally, thirty-five blood proteins were commonly identified among all studied samples. These proteins included serine protease inhibitors, such as alpha-1-antitrypsin, alpha-1-antichymotrypsin, alpha-1-acid glycoprotein, inter-alpha-trypsin-inhibitor, protease C1 inhibitor, and complement proteins. In addition, abundant presence of immunoglobulin G was observed. The abundance of albumin, haptoglobin, ceruloplasmin vitronectin, fetuin-A, ficolin-3 and transthyretin was also detected. Conclusion: The results of this study indicated that PRF abundantly contains blood-origin actors which were previously reported for their direct contribution to wound healing. Further studies exploring the protein content of PRF are needed to reveal its undisclosed potential roles in the healing process. Keywords: Platelet-rich fibrin, Proteomics, MALDI, Blood proteins